123456789101112131415161718192021222324252627282930313233343536373839404142434445464748495051525354555657585960616263646566676869707172737475767778798081828384858687888990919293949596979899100101102103104105106107108109110111112113114115116117118119120121122123124125126127128129130131132133134135136137138139140141142143144145146147148149150151152153154155156157158159160161162163164165166167168169170171172173174175176177178179180181182183184185186187188189190191 |
- from sympy.core.numbers import (I, pi, Rational)
- from sympy.core.singleton import S
- from sympy.core.symbol import symbols
- from sympy.functions.elementary.exponential import exp
- from sympy.functions.elementary.miscellaneous import sqrt
- from sympy.functions.elementary.trigonometric import (cos, sin)
- from sympy.functions.special.spherical_harmonics import Ynm
- from sympy.matrices.dense import Matrix
- from sympy.physics.wigner import (clebsch_gordan, wigner_9j, wigner_6j, gaunt,
- real_gaunt, racah, dot_rot_grad_Ynm, wigner_3j, wigner_d_small, wigner_d)
- from sympy.testing.pytest import raises
- # for test cases, refer : https://en.wikipedia.org/wiki/Table_of_Clebsch%E2%80%93Gordan_coefficients
- def test_clebsch_gordan_docs():
- assert clebsch_gordan(Rational(3, 2), S.Half, 2, Rational(3, 2), S.Half, 2) == 1
- assert clebsch_gordan(Rational(3, 2), S.Half, 1, Rational(3, 2), Rational(-1, 2), 1) == sqrt(3)/2
- assert clebsch_gordan(Rational(3, 2), S.Half, 1, Rational(-1, 2), S.Half, 0) == -sqrt(2)/2
- def test_clebsch_gordan():
- # Argument order: (j_1, j_2, j, m_1, m_2, m)
- h = S.One
- k = S.Half
- l = Rational(3, 2)
- i = Rational(-1, 2)
- n = Rational(7, 2)
- p = Rational(5, 2)
- assert clebsch_gordan(k, k, 1, k, k, 1) == 1
- assert clebsch_gordan(k, k, 1, k, k, 0) == 0
- assert clebsch_gordan(k, k, 1, i, i, -1) == 1
- assert clebsch_gordan(k, k, 1, k, i, 0) == sqrt(2)/2
- assert clebsch_gordan(k, k, 0, k, i, 0) == sqrt(2)/2
- assert clebsch_gordan(k, k, 1, i, k, 0) == sqrt(2)/2
- assert clebsch_gordan(k, k, 0, i, k, 0) == -sqrt(2)/2
- assert clebsch_gordan(h, k, l, 1, k, l) == 1
- assert clebsch_gordan(h, k, l, 1, i, k) == 1/sqrt(3)
- assert clebsch_gordan(h, k, k, 1, i, k) == sqrt(2)/sqrt(3)
- assert clebsch_gordan(h, k, k, 0, k, k) == -1/sqrt(3)
- assert clebsch_gordan(h, k, l, 0, k, k) == sqrt(2)/sqrt(3)
- assert clebsch_gordan(h, h, S(2), 1, 1, S(2)) == 1
- assert clebsch_gordan(h, h, S(2), 1, 0, 1) == 1/sqrt(2)
- assert clebsch_gordan(h, h, S(2), 0, 1, 1) == 1/sqrt(2)
- assert clebsch_gordan(h, h, 1, 1, 0, 1) == 1/sqrt(2)
- assert clebsch_gordan(h, h, 1, 0, 1, 1) == -1/sqrt(2)
- assert clebsch_gordan(l, l, S(3), l, l, S(3)) == 1
- assert clebsch_gordan(l, l, S(2), l, k, S(2)) == 1/sqrt(2)
- assert clebsch_gordan(l, l, S(3), l, k, S(2)) == 1/sqrt(2)
- assert clebsch_gordan(S(2), S(2), S(4), S(2), S(2), S(4)) == 1
- assert clebsch_gordan(S(2), S(2), S(3), S(2), 1, S(3)) == 1/sqrt(2)
- assert clebsch_gordan(S(2), S(2), S(3), 1, 1, S(2)) == 0
- assert clebsch_gordan(p, h, n, p, 1, n) == 1
- assert clebsch_gordan(p, h, p, p, 0, p) == sqrt(5)/sqrt(7)
- assert clebsch_gordan(p, h, l, k, 1, l) == 1/sqrt(15)
- def test_wigner():
- def tn(a, b):
- return (a - b).n(64) < S('1e-64')
- assert tn(wigner_9j(1, 1, 1, 1, 1, 1, 1, 1, 0, prec=64), Rational(1, 18))
- assert wigner_9j(3, 3, 2, 3, 3, 2, 3, 3, 2) == 3221*sqrt(
- 70)/(246960*sqrt(105)) - 365/(3528*sqrt(70)*sqrt(105))
- assert wigner_6j(5, 5, 5, 5, 5, 5) == Rational(1, 52)
- assert tn(wigner_6j(8, 8, 8, 8, 8, 8, prec=64), Rational(-12219, 965770))
- # regression test for #8747
- half = S.Half
- assert wigner_9j(0, 0, 0, 0, half, half, 0, half, half) == half
- assert (wigner_9j(3, 5, 4,
- 7 * half, 5 * half, 4,
- 9 * half, 9 * half, 0)
- == -sqrt(Rational(361, 205821000)))
- assert (wigner_9j(1, 4, 3,
- 5 * half, 4, 5 * half,
- 5 * half, 2, 7 * half)
- == -sqrt(Rational(3971, 373403520)))
- assert (wigner_9j(4, 9 * half, 5 * half,
- 2, 4, 4,
- 5, 7 * half, 7 * half)
- == -sqrt(Rational(3481, 5042614500)))
- def test_gaunt():
- def tn(a, b):
- return (a - b).n(64) < S('1e-64')
- assert gaunt(1, 0, 1, 1, 0, -1) == -1/(2*sqrt(pi))
- assert isinstance(gaunt(1, 1, 0, -1, 1, 0).args[0], Rational)
- assert isinstance(gaunt(0, 1, 1, 0, -1, 1).args[0], Rational)
- assert tn(gaunt(
- 10, 10, 12, 9, 3, -12, prec=64), (Rational(-98, 62031)) * sqrt(6279)/sqrt(pi))
- def gaunt_ref(l1, l2, l3, m1, m2, m3):
- return (
- sqrt((2 * l1 + 1) * (2 * l2 + 1) * (2 * l3 + 1) / (4 * pi)) *
- wigner_3j(l1, l2, l3, 0, 0, 0) *
- wigner_3j(l1, l2, l3, m1, m2, m3)
- )
- threshold = 1e-10
- l_max = 3
- l3_max = 24
- for l1 in range(l_max + 1):
- for l2 in range(l_max + 1):
- for l3 in range(l3_max + 1):
- for m1 in range(-l1, l1 + 1):
- for m2 in range(-l2, l2 + 1):
- for m3 in range(-l3, l3 + 1):
- args = l1, l2, l3, m1, m2, m3
- g = gaunt(*args)
- g0 = gaunt_ref(*args)
- assert abs(g - g0) < threshold
- if m1 + m2 + m3 != 0:
- assert abs(g) < threshold
- if (l1 + l2 + l3) % 2:
- assert abs(g) < threshold
- assert gaunt(1, 1, 0, 0, 2, -2) is S.Zero
- def test_realgaunt():
- # All non-zero values corresponding to l values from 0 to 2
- for l in range(3):
- for m in range(-l, l+1):
- assert real_gaunt(0, l, l, 0, m, m) == 1/(2*sqrt(pi))
- assert real_gaunt(1, 1, 2, 0, 0, 0) == sqrt(5)/(5*sqrt(pi))
- assert real_gaunt(1, 1, 2, 1, 1, 0) == -sqrt(5)/(10*sqrt(pi))
- assert real_gaunt(2, 2, 2, 0, 0, 0) == sqrt(5)/(7*sqrt(pi))
- assert real_gaunt(2, 2, 2, 0, 2, 2) == -sqrt(5)/(7*sqrt(pi))
- assert real_gaunt(2, 2, 2, -2, -2, 0) == -sqrt(5)/(7*sqrt(pi))
- assert real_gaunt(1, 1, 2, -1, 0, -1) == sqrt(15)/(10*sqrt(pi))
- assert real_gaunt(1, 1, 2, 0, 1, 1) == sqrt(15)/(10*sqrt(pi))
- assert real_gaunt(1, 1, 2, 1, 1, 2) == sqrt(15)/(10*sqrt(pi))
- assert real_gaunt(1, 1, 2, -1, 1, -2) == -sqrt(15)/(10*sqrt(pi))
- assert real_gaunt(1, 1, 2, -1, -1, 2) == -sqrt(15)/(10*sqrt(pi))
- assert real_gaunt(2, 2, 2, 0, 1, 1) == sqrt(5)/(14*sqrt(pi))
- assert real_gaunt(2, 2, 2, 1, 1, 2) == sqrt(15)/(14*sqrt(pi))
- assert real_gaunt(2, 2, 2, -1, -1, 2) == -sqrt(15)/(14*sqrt(pi))
- assert real_gaunt(-2, -2, -2, -2, -2, 0) is S.Zero # m test
- assert real_gaunt(-2, 1, 0, 1, 1, 1) is S.Zero # l test
- assert real_gaunt(-2, -1, -2, -1, -1, 0) is S.Zero # m and l test
- assert real_gaunt(-2, -2, -2, -2, -2, -2) is S.Zero # m and k test
- assert real_gaunt(-2, -1, -2, -1, -1, -1) is S.Zero # m, l and k test
- x = symbols('x', integer=True)
- v = [0]*6
- for i in range(len(v)):
- v[i] = x # non literal ints fail
- raises(ValueError, lambda: real_gaunt(*v))
- v[i] = 0
- def test_racah():
- assert racah(3,3,3,3,3,3) == Rational(-1,14)
- assert racah(2,2,2,2,2,2) == Rational(-3,70)
- assert racah(7,8,7,1,7,7, prec=4).is_Float
- assert racah(5.5,7.5,9.5,6.5,8,9) == -719*sqrt(598)/1158924
- assert abs(racah(5.5,7.5,9.5,6.5,8,9, prec=4) - (-0.01517)) < S('1e-4')
- def test_dot_rota_grad_SH():
- theta, phi = symbols("theta phi")
- assert dot_rot_grad_Ynm(1, 1, 1, 1, 1, 0) != \
- sqrt(30)*Ynm(2, 2, 1, 0)/(10*sqrt(pi))
- assert dot_rot_grad_Ynm(1, 1, 1, 1, 1, 0).doit() == \
- sqrt(30)*Ynm(2, 2, 1, 0)/(10*sqrt(pi))
- assert dot_rot_grad_Ynm(1, 5, 1, 1, 1, 2) != \
- 0
- assert dot_rot_grad_Ynm(1, 5, 1, 1, 1, 2).doit() == \
- 0
- assert dot_rot_grad_Ynm(3, 3, 3, 3, theta, phi).doit() == \
- 15*sqrt(3003)*Ynm(6, 6, theta, phi)/(143*sqrt(pi))
- assert dot_rot_grad_Ynm(3, 3, 1, 1, theta, phi).doit() == \
- sqrt(3)*Ynm(4, 4, theta, phi)/sqrt(pi)
- assert dot_rot_grad_Ynm(3, 2, 2, 0, theta, phi).doit() == \
- 3*sqrt(55)*Ynm(5, 2, theta, phi)/(11*sqrt(pi))
- assert dot_rot_grad_Ynm(3, 2, 3, 2, theta, phi).doit().expand() == \
- -sqrt(70)*Ynm(4, 4, theta, phi)/(11*sqrt(pi)) + \
- 45*sqrt(182)*Ynm(6, 4, theta, phi)/(143*sqrt(pi))
- def test_wigner_d():
- half = S(1)/2
- alpha, beta, gamma = symbols("alpha, beta, gamma", real=True)
- d = wigner_d_small(half, beta).subs({beta: pi/2})
- d_ = Matrix([[1, 1], [-1, 1]])/sqrt(2)
- assert d == d_
- D = wigner_d(half, alpha, beta, gamma)
- assert D[0, 0] == exp(I*alpha/2)*exp(I*gamma/2)*cos(beta/2)
- assert D[0, 1] == exp(I*alpha/2)*exp(-I*gamma/2)*sin(beta/2)
- assert D[1, 0] == -exp(-I*alpha/2)*exp(I*gamma/2)*sin(beta/2)
- assert D[1, 1] == exp(-I*alpha/2)*exp(-I*gamma/2)*cos(beta/2)
|